Staple-Line Reinforcement of the Duodenal Stump With Intracorporeal Lembert's Sutures in Laparoscopic Distal Gastrectomy With Roux-en-Y Reconstruction for Gastric Cancer. Issue 4 (August 2016) - Inoue, Kentaro; Michiura, Taku; Fukui, Junichi; Mukaide, Hiromi; Ozaki, Takashi; Miki, Hirokazu; Kobayashi, Toshinori; Oishi, Masaharu; Inada, Ryo; Matsumoto, Tomoko; Yamada, Masanori; Yanagimoto, Hiroaki; et al.
Abstract : Purpose: We report a duodenal stump reinforcement procedure in laparoscopic distal gastrectomy with Roux-en-Y reconstruction. Methods: We retrospectively reviewed the data of 223 patients who underwent laparoscopic distal gastrectomy with Roux-en-Y reconstruction for gastric cancer. We compared 2 groups: group NR (not reinforced, n=102, June 2009 to December 2011) when we did not perform reinforcement of the duodenal stump, and group R (reinforced, n=121, January 2012 to July 2014) when we did the reinforcement. The duodenum was divided with an endoscopic linear stapler. In group R, the duodenal staple line was reinforced by hand-sewn Lembert's sutures. Results: There were no significant differences between group NR and R in patients' characteristics. Duodenal stump leakage occurred in 2 patients in group NR (2.0%). By contrast, in R group, no patients had duodenal stump leakage or fistula. Conclusions: Duodenal stump leakage can be avoided by using reinforcement with Lembert's sutures. Abstract : Supplemental Digital Content is available in the text.